THE USE OF PHONOPHORESIS IN DISEASES OF THE MUSCULOSKELETAL SYSTEM (Fiep Bulletin - online, 2024)
Introduction: The use of ultrasound (US) in different applications in the health sector has gained prominence, due to the fact that US can be used as an energy source for the occurrence of chemical reactions. US has different forms of use, at the most varied frequencies, and in the area of ​​physiotherapy its use occurs at frequencies of 1 and 3 MHz. In physiotherapy, therapeutic ultrasound consists of using the device for thermal effects in the region that needs treatment : reduced pain, reduced muscle spasms, increased tissue extensibility and improved local blood flow. Phonophoresis is a technique that facilitates skin penetration through ultrasonic energy in the disorganization of the lipid structure of the epidermis, using it as a means of contact between the head of the device and the skin with medication. The objective of the present study is to investigate and highlight the effect of using phonophoresis on musculoskeletal changes.Methods: This research is qualitative with a documentary/bibliographical characteristic, with consultations with the Medical Literature Analysis and Retrieval Sistem Online (MedLine/PubMed), Biomedical Answers (EMBASE), Latin American and Caribbean Literature in Health Sciences (LILACS), the Scientific Electronic Library Online (SciELO), the Physiotherapy Evidence Database and the Virtual Health Library (VHL). Articles were obtained using the following keywords: “therapeutic ultrasound”, “physiotherapy”, “phonophoresis”, “musculoskeletal system”, under the Boolean operators “and” and “or”. Additional studies were achieved through searches common from references in Portuguese or English, acquired in the articles obtained.Results: the results and outcomes of the chosen studies, it was observed that the majority of these studies use similar outcomes. As a result, in summary, most studies concluded that the use of phonophoresis was effective for the outcomes evaluated, in the short term, and especially that this treatment was effective, facilitating the reduction of inflammation and pain and musculoskeletal changes.Conclusion:All studies showed a positive effect of phonophoresis in relieving pain, reducing joint stiffness, improving functional capacity and physical function in musculoskeletal disorders.